2006
DOI: 10.1002/cncr.21769
|View full text |Cite
|
Sign up to set email alerts
|

Severity, risk factors, and physician practices in the management of anemia during concurrent chemoradiation for head and neck carcinoma

Abstract: BACKGROUND. Anemia is a well-recognized complication of concurrent chemora-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…In previous studies, prechemotherapy Hgb level was the most commonly reported risk factor for anemia on treatment or requirement for transfusion [1, 6,9,18]. Other reported risk factors include age older than 65 [11], hemoglobin decrease during the first month of chemotherapy [6], duration of chemotherapy [6], tumor type [1, 6], previous transfusions [6,7], platinum-based chemotherapy [1] and platinum pharmacokinetics [23], multiple concurrent chemotherapeutic agents [25], female sex [1], performance status (PS)>1 [24], pretreatment absolute lymphocyte count (ALC) lower than 700/μl [24]. Our data set did not permit us to test all these reported risk factors, but our results are consistent.…”
Section: Discussionmentioning
confidence: 98%
“…In previous studies, prechemotherapy Hgb level was the most commonly reported risk factor for anemia on treatment or requirement for transfusion [1, 6,9,18]. Other reported risk factors include age older than 65 [11], hemoglobin decrease during the first month of chemotherapy [6], duration of chemotherapy [6], tumor type [1, 6], previous transfusions [6,7], platinum-based chemotherapy [1] and platinum pharmacokinetics [23], multiple concurrent chemotherapeutic agents [25], female sex [1], performance status (PS)>1 [24], pretreatment absolute lymphocyte count (ALC) lower than 700/μl [24]. Our data set did not permit us to test all these reported risk factors, but our results are consistent.…”
Section: Discussionmentioning
confidence: 98%
“…28 Of note, approximately 80% of patients with HNC may develop mild-to-severe anaemia that has a negative impact on treatment tolerance and causes treatment failure. 29 Moreover, smoking may aggravate anaemia in patients with lung and HNCs. Therefore, WHO recommends evaluating 'smoking-adjusted anaemia'.…”
Section: Discussionmentioning
confidence: 99%
“…8,31 The immediacy of the effect of RBC transfusions makes them particularly useful when treating patients with life-threatening anaemia. 32 It is also the treatment recommended in the current ASCO and the ASH guidelines for severe anaemia (defined as a Hb level of <8 g/dL).…”
Section: Rbc Transfusion For the Treatment Of Cia In Elderly Patientsmentioning
confidence: 99%